2022
DOI: 10.5559/di.31.4.06
|View full text |Cite
|
Sign up to set email alerts
|

Online Video Game Influencer's Credibility and Purchase Intention

Abstract: In the last few years, and especially during the COVID-19 pandemic, the majority of everyday activities were shifted online. Therefore, marketing strategies had to adapt to this shift. This led to the development of new forms of marketing, including influencer marketing. Although credibility is often theorised as the reason why the audience prefers to follow influencers over celebrities, empirical evidence is mixed and unrelated to the gaming industry. Therefore, our aim in this study was to test if source cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Typically, reviews of video games can be divided into two types based on the information source, namely user-generated reviews and influencer reviews [5][6][7]. Compared to ordinary users, influencers are perceived to be more trustworthy and credible because they are experts and experienced in the specific area, and have a high level of source credibility [8][9]. Therefore, influencer reviews are identified as outweighing ordinary user-generated reviews in the video game domain [5].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, reviews of video games can be divided into two types based on the information source, namely user-generated reviews and influencer reviews [5][6][7]. Compared to ordinary users, influencers are perceived to be more trustworthy and credible because they are experts and experienced in the specific area, and have a high level of source credibility [8][9]. Therefore, influencer reviews are identified as outweighing ordinary user-generated reviews in the video game domain [5].…”
Section: Introductionmentioning
confidence: 99%